Development of a nano-satellite attitude control system - Tan, Zhenyang (2014)
Satellite industry is rapidly making big steps in Singapore in the last decade especially with the launch of X-Sat, Singapore’s first ever locally designed satellite and VELOX-PII, wholly designed and built by Nanyang Technological University (NTU) students. As detailed information such as specifications of designs on satellites from the external international sources are strictly confidential and limited, Singapore has to do the research and testing on her own while seeking additional advice from overseas research partners.